Les soft skills au cœur de la révolution éducative - Daniel Peyron; Robert Lanquar (Études Caribéennes)
The importance of values and soft skills has since been recognized in professional success as well as in personal life (family, social and civic). Human Resources Directors (HRDs) do not fail to remind this in all their investigations. The acceleration of globalization in recent decades has complicated the challenge: working with multidisciplinary and intercultural teams in several languages, in a multi-site landscape, in project mode, at the crossroads of very varied geopolitical universes ... The educational response has been uneven from one country to another... and to take the case of France, if many initiatives have emerged in Higher Education, there have been few developments in High School Education where educational issues on values and behaviors are decisive. The COVID -19 pandemic has revealed that "caring for others" is becoming an absolute necessity, even a matter of survival, for oneself and for others, and that well-being is a collective success, within an ecosystem to which everyone must provide support and value. OECD, in its Future of Education and Skills Report - 2030 Project- calls for broader goals for education: individual and collective well-being and asks to develop the learner's capacity to act “taking his/her place in the world and exert a positive influence on others, events and circumstances". What are the soft skills that will enable individuals and the communities and territories where they live to better adapt to the consequences of the COVID-19 crisis? What reflections should then be carried out on the possible pedagogical levers to answer these questions, with a particular focus on the interface between Secondary and Higher Education? What research needs to be undertaken to answer them? How to conduct international relations to face the challenges of soft skills? What solidarity and attention to the other should be put forward to achieve this internationally? For example, how can tourism practices be better used to integrate the learning of soft skills?